Multi-Electrode Alpha tACS During Varying Background Tasks Fails to Modulate Subsequent Alpha Power - Fekete, Tomer; Nikolaev, Andrey R.; De Knijf, Floris; Zharikova, Aleksandra; van Leeuwen, Cees (Frontiers in Neuroscience, 2018)
Transcranial alternating-current stimulation (tACS) for entraining alpha activity holds potential for influencing mental function, both in laboratory and clinical settings. While initial results of alpha entrainment are promising, questions remain regarding its translational potential—namely if tACS alpha entrainment is sufficiently robust to context and to what extent it can be upscaled to multi-electrode arrangements needed to direct currents into precise brain loci. We set out to explore these questions by administering alternating current through a multi-electrode montage (mtACS), while varying background task. A multi-electrode analog of previously employed anterior/posterior stimulation failed to replicate the reported alpha entrainment, suggesting that further work is required to understand the scope of applicability of tACS alpha entrainment.